Sternal bone marrow derived equine multipotent mesenchymal stromal cells (MSCs): investigations considering the sampling site and the use of different culture media. Issue 3 (20th June 2016) - Eydt, Carina; Geburek, Florian; Schröck, Carmen; Hambruch, Nina; Rohn, Karl; Pfarrer, Christiane; Staszyk, Carsten
Abstract: Aspiration of equine sternal bone marrow is required for the cultivation of bone marrow‐derived multipotent mesenchymal stromal cells (BM‐MSCs) for regenerative therapies. For bone marrow aspiration as well as for MSC cultivation, there is a need to optimize techniques and protocols to enhance MSC harvest at minimized culture times. In a comparative study bone marrow aspirates from sternebra 4 and 5 were collected at two different positions within the sternebrae, either from 10 mm or from 30 mm dorsal from the ventral margin of the sternebrae. Accuracy of the puncture depth was confirmed by ultrasonography and computed tomography. Isolated MSCs were cultivated using media supplemented with three alternative sera, i.e. fetal calf serum, standardized horse serum and autologous serum. Due to morphological characteristics (spherical shape, only thin layer of hyaline cartilage at the ventral site, reliable bone marrow aspiration from only 10 mm intraosseous depth), sternebra 5 appeared most suitable for bone marrow aspiration. Cultivation and expansion of BM‐MSCs was most efficient using fetal calf serum. Abstract : Equine sternal bone marrow was aspirated from sternebra 4 and 5 at two different positions within the sternebrae. Isolated MSCs were cultivated using media supplemented with three alternative sera. Harvest of bone marrow appeared most suitable from sternebra 5 at an intraosseus depth of 10 mm, cultivation and expansion of BM‐MSC was most successful using fetal calf serum.